Towards a standard procedure for the measurement of the multi-photon component in a CW telecom heralded single-photon source. (22nd February 2019) - Rebufello, E; Piacentini, F; López, M; Kirkwood, R A; Ruo Berchera, I; Gramegna, M; Brida, G; Kück, S; Chunnilall, C J; Genovese, M; Degiovanni, I P
Abstract: Single-photon sources are set to be a fundamental tool for metrological applications as well as for quantum information related technologies. Because of their upcoming widespread dissemination, the need for their characterization and standardization is becoming of the utmost importance. Here, we illustrate a strategy to provide a quantitative estimate of the multi-photon component of a single-photon source, showing the results achieved in a pilot study for the measurement of the second-order autocorrelation function g (2) (0) of a low-noise CW heralded single photon source prototype (operating at telecom wavelength nm) realized in INRiM. The results of this pilot study, involving INRiM, NPL and PTB, will help to build a robust and unambiguous procedure for the characterization of the emission of a single-photon source.